2021
DOI: 10.1186/s13046-021-02036-z
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular traps in cancer: not only catching microbes

Abstract: Neutrophils are the most abundant type of white blood cells circulating throughout the bloodstream and are often considered the frontline defenders in innate immunity. However, neutrophils are increasingly being recognized as having an important role in tumorigenesis and carcinogenesis due to their aberrant activation by molecules released into the tumor microenvironment. One defensive response of neutrophils that is aberrantly triggered during the neoplastic process is called NETosis, where activated neutroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
86
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(87 citation statements)
references
References 60 publications
1
86
0
Order By: Relevance
“…Particularly, Clark and colleagues have initially shown that TLR-4-activated platelets trigger vital NET formation in order to capture bacteria in septic blood ( 45 ), while subsequent in vitro and in vivo work by the same laboratory demonstrated vital NET release and involvement of TLR-2 and complement receptor 3 upon neutrophil stimulation with Gram-positive bacteria ( 7 , 43 ). Similar to suicidal NETosis, vital NET formation has also been shown to be partially dependent on calcium influx and activated PAD4 and NE, both of which migrate to the nucleus to initiate unpacking of histones and chromatin decondensation ( Figure 1 ) ( 28 , 46 ). Subsequently, nuclear envelope blebbing leads to the formation of DNA-containing vesicles that eventually fuse with the plasma membrane to expel their antimicrobial content into the extracellular space ( Figure 1 ) ( 44 ).…”
Section: Molecular Mechanisms Of Suicidal Netosis and Vital Net Forma...mentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, Clark and colleagues have initially shown that TLR-4-activated platelets trigger vital NET formation in order to capture bacteria in septic blood ( 45 ), while subsequent in vitro and in vivo work by the same laboratory demonstrated vital NET release and involvement of TLR-2 and complement receptor 3 upon neutrophil stimulation with Gram-positive bacteria ( 7 , 43 ). Similar to suicidal NETosis, vital NET formation has also been shown to be partially dependent on calcium influx and activated PAD4 and NE, both of which migrate to the nucleus to initiate unpacking of histones and chromatin decondensation ( Figure 1 ) ( 28 , 46 ). Subsequently, nuclear envelope blebbing leads to the formation of DNA-containing vesicles that eventually fuse with the plasma membrane to expel their antimicrobial content into the extracellular space ( Figure 1 ) ( 44 ).…”
Section: Molecular Mechanisms Of Suicidal Netosis and Vital Net Forma...mentioning
confidence: 99%
“…To date, two predominant pathways have been described in detail that lead to the expulsion of NETs from neutrophils: suicidal (lytic) NETosis, which causes neutrophil cell death, and vital NET formation that results in the release of NET-loaded vesicles from viable PMNs ( Figure 1 ) ( 21 , 28 ). Suicidal NETosis, a process that provokes NET formation within 3-4 hours post-stimulation ( 23 ), largely depends on calcium signaling along with the protein kinase C (PKC)- or Raf-MEK-ERK pathway-dependent activation of the membrane-bound NADPH oxidase, which represents a multisubunit protein complex that synthesizes ROS for the subsequent activation of PAD4 (protein-arginine deiminase type 4) ( Figure 1 ) ( 6 , 21 , 23 , 29 , 30 ).…”
Section: Molecular Mechanisms Of Suicidal Netosis and Vital Net Forma...mentioning
confidence: 99%
“…It has been shown that myocarditis cardiotoxicity is related to activated T cells [ 100 ], and less than 50% of patients have been reported to respond to high doses of immunosuppressants or corticosteroids [ 27 , 101 ]. NETs molecules have been proposed as mechanisms of immunotherapy resistance and potential targets for emerging candidate drugs [ 102 ]. It has been further suggested that a high number of tumor-associated neutrophils in the tumor microenvironment, as well as aberrant NETs release, indicate poor response to immunotherapies for several cancers.…”
Section: Effects Of Cancer Treatments On Neutrophil Amount Accumulati...mentioning
confidence: 99%
“…The increased number of tumor associated neutrophils is linked to poor outcomes in different type of cancers, and many patients with advanced cancer show high levels of blood neutrophils (5,6,7). It has been shown that various tumors are capable to predispose circulating neutrophils to produce neutrophil extracellular traps (NETs) causing systemic thrombosis and thromboembolism which are often associated with human cancers, through biological process called NETosis (4,8,9,10,11,12,13,14). NETs are composed of nuclear DNA in a web-like structures extruded from neutrophils and mixed with granular and some cytoplasmic constituents, such as neutrophil elastase (NE), myeloperoxidase (MPO), and citrullinated histone H3 (citH3), in response to infection or cancer burden (15).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have unveiled unexpected functions of NETosis in promoting tumor development including tumor growth, metastasis and angiogenesis and in protecting tumor cells from cytotoxic immune cells (16, 17,18,19,20,12,21,22). These evidences suggest that NETosis may provide a novel tool, potentially targetable, for cancer treatment (23,24,25,14). Moreover, several studies indicate that the mechanism of NETosis can provide an explanation for the elevated circulating cell-free DNA (cfDNA) release in blood stream in pathologic conditions (26,27) and strongly suggest that these NET-associated molecules are potential tumour biomarkers (5,28,29,30).…”
Section: Introductionmentioning
confidence: 99%